Fidelity of a Bacterial DNA Polymerase in Microgravity, a Model for Human Health in Space - Aaron H Rosenstein (Frontiers Media S.A., 2021)
Long-term space missions will expose crew members, their cells as well as their microbiomes to prolonged periods of microgravity and ionizing radiation, environmental stressors for which almost no earth-based organisms have evolved to survive. Despite the importance of maintaining genomic integrity, the impact of these stresses on DNA polymerase-mediated replication and repair has not been fully explored. DNA polymerase fidelity and replication rates were assayed under conditions of microgravity generated by parabolic flight and compared to earth-like gravity. Upon commencement of a parabolic arc, primed synthetic single-stranded DNA was used as a template for one of two enzymes (Klenow fragment exonuclease+/−; with and without proofreading exonuclease activity, respectively) and were quenched immediately following the 20 s microgravitational period. DNA polymerase error rates were determined with an algorithm developed to identify experimental mutations. In microgravity Klenow exonuclease+ showed a median 1.1-fold per-base decrease in polymerization fidelity for base substitutions when compared to earth-like gravity (p = 0.02), but in the absence of proofreading activity, a 2.4-fold decrease was observed (p = 1.98 × 10−11). Similarly, 1.1-fold and 1.5-fold increases in deletion frequencies in the presence or absence of exonuclease activity (p = 1.51 × 10−7 and p = 8.74 × 10−13), respectively, were observed in microgravity compared to controls. The development of this flexible semi-autonomous payload system coupled with genetic and bioinformatic approaches serves as a proof-of-concept for future space health research.